"I have to start all over again": The role of institutional and personal arrival infrastructures in refugees' home-making processes in Amsterdam - Mieke Kox; Ilse van Liempt (Comparative Population Studies (CPoS), 2022)
In this study, we take the concept of arrival infrastructures as a starting point to explore refugees' home-making processes in Amsterdam. This concept allows us to look beyond formal infrastructures set up for refugees and to take a closer look at all (f)actors playing a role in refugees' processes of "starting all over again". Drawing on participatory ethnographic research in a community centre for refugees, we describe the role of institutional as well as personal infrastructures in material and affective terms and show how these are related to refugees' sense of belonging in the city. We illustrate that refugees become entangled in a web of reception/asylum seekers centres and civic integration requirements that facilitate and constrain their home-making processes in a new place. It is more the informal, personal infrastructures that enable refugees to build social and affective ties in the city. Nevertheless, refugees are still struggling with social isolation and a lack of participation due to their limited opportunities and the relatively closed character of Dutch society. This impacts their sense of belonging and comes at the cost of their integration in the city. These insights raise not only questions on the current organisation of arrival infrastructures for refugees, but also show the need to move towards a multidimensional integration model that includes the role of (civil) society in the destination society in the refugees' integration processes.
urn:nbn:de:bib-cpos-2022-07en8
Keywords: 300; Arrival infrastructures; Home-making processes; Belonging; Integration; Refugees; Cities